Measure, and Predict Shifts in Urban Land Usage in Jorhat District: Examining the Impact of River Dynamics on Urban Land Use in Jorhat District (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The river bed is very narrow and, as a result, the river reaches the danger point within 12 hours of precipitation during the flood season. The river has a strong propensity to alter its courses during heavy flood times owing to the shallowness of the river portion and low lying adjoining regions. J Orhat and its suburbs were flooded in May 1977 owing to unprecedented and concentrated rainfall. Owing to poor drainage of the Tocklai and Tarajan drains, the problem was further exacerbated. It has created flood congestion due to the backwater movement of the river through the Tocklai canal, triggering floods and water logging in most areas of Jorhat, as the bed of the river Bhogdoi is higher than the level of the district. Thus, it has been shown that the intervention of man with natural drainage and its impact is maybe no more plainly evident than in the town of Jorhat. The embankment along the river Bhogodi has proven to be both a blessing and a curse for the region. They are helpful in the way that they shield the metropolitan environment from destructive flooding, but they are a curse since they do not enable water to be pumped out easily and therefore trigger water-logging in city areas. In comparison, the rise in the development of the city's badly drained low-lying zones, where no technological drainage scheme has been implemented, has rendered the problem worse. Following heavy rainfall, water-logging in the low-lying areas has become a frequent feature during the rainy seasons.